2015
DOI: 10.1111/cod.12436
|View full text |Cite
|
Sign up to set email alerts
|

Chromium allergy and dermatitis: prevalence and main findings

Abstract: SummaryThe history of chromium as an allergen goes back more than a century, and includes an interventional success with national legislation that led to significant changes in the epidemiology of chromium allergy in construction workers. The 2015 EU Leather Regulation once again put a focus on chromium allergy, emphasizing that the investigation of chromium allergy is still far from complete. Our review article on chromium focuses on the allergen's chemical properties, its potential exposure sources, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 186 publications
3
84
0
5
Order By: Relevance
“…Reactions to cobalt chloride and potassium dichromate were also frequent among the children with AD. Previous studies have reported the same pattern of sensitization in patients with AD . In a study by Malajian and Belsito, positive patch test reactions to nickel sulfate, cobalt chloride and potassium dichromate were significantly more frequent among patients with AD than in controls.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Reactions to cobalt chloride and potassium dichromate were also frequent among the children with AD. Previous studies have reported the same pattern of sensitization in patients with AD . In a study by Malajian and Belsito, positive patch test reactions to nickel sulfate, cobalt chloride and potassium dichromate were significantly more frequent among patients with AD than in controls.…”
Section: Discussionsupporting
confidence: 54%
“…In a study by Malajian and Belsito, positive patch test reactions to nickel sulfate, cobalt chloride and potassium dichromate were significantly more frequent among patients with AD than in controls. The three metal allergens are known to occur concomitantly, and the irritating properties of potassium dichromate could in theory cause a false‐positive reaction in AD skin . However, especially reactions to potassium dichromate were relevant in a substantial proportion of the reviewed cases .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of chromate contact allergy is decreasing in Europe, probably as a result of the legislative measures regarding hexavalent chromium in cement , but cases of chromate allergy among concrete workers are still being observed . Whereas cement has been a historically important source of sensitization in Europe, it is currently thought that exposure to chromium‐tanned leather is of greater importance .…”
Section: Discussionmentioning
confidence: 99%
“…It may present acutely as an initial sensitization after exposure to the allergen or may be seen in a previously sensitized individual on re-exposure. The epidemiology of contact dermatitis has been analyzed in various studies done in the past from almost all over the world [14], but no such data from Kuwait exists. Nickel is the most common identified allergen worldwide, and is extensively used in everyday life.…”
Section: Introductionmentioning
confidence: 99%